Posizioni Selvagge. - Galleria Peccolo, Livorno (Livorno : Galleria Peccolo, 1987)
Stupica, Gabrijel ; Fassianos, Alekos ; Meloni, Gino ; Balzer, Mathias ; Macreau, Michel ; Saul, Peter ; Wilson, Scottie ; Zagajewski, Stanislaw ; Wölfli, Adolf ; Schroeder-Sonnenstern, Friedrich
Posizioni Selvagge, Galleria Peccolo, Livorno, 1987
boek